Bacterial cellulose-laponite clay nanocomposites - Perotti, Gustavo F.; Barud, Hernane S. [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Constantino, Vera R. L. (Elsevier B.V., 2011)
A novel material comprised of bacterial cellulose (BC) and Laponite clay with different inorganic organic ratios (m/m) was prepared by the contact of never-dried membranes of BC with a previous dispersion of clay particles in water. Field emission scanning electron microscopy (FE-SEM) data of composite materials revealed an effective adhesion of clay over the surface of BC membrane; inorganic particles also penetrate into the polymer bulk, with a significant change of the surface topography even at 5% of clay loading. As a consequence, the mechanical properties are deeply affected by the presence of clay, increasing the values of the Young modulus and the tensile strength. However the maximum strain is decreased when the clay content is increased in the composite in comparison to pristine BC. The main weight loss step of the composites is shifted towards higher temperatures compared to BC, indicating that the clay particles slightly protect the polymer from thermal and oxidative decomposition. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Bacterial cellulose; Clay; Nanocomposites